A Landscape Lullaby? The Function of (Post-) Pastoral Elements in Kazuo Ishiguro's Never Let Me Go - Musial, Lisa (Satura, 2018)
Published in 2005, Kazuo Ishiguro’s novel Never Let Me Go presents a vision of a society where clones are raised to donate their vital organs. Because of the dystopian elements in the narration, one might expect a setting in a futuristic environment. Instead, the story takes place mainly in pastoral visions of the English countryside. This distinct setting creates a stark contrast to the characters’ harsh reality, which is gradually revealed throughout the narrative. In this article, I argue that the novel complicates the pastoral and offers new perspectives on the relationship of humans and nature by incorporating post-pastoral elements. In order to investigate the contrast between the dystopian reality and its peaceful setting, the pastoral initially provides a useful lens. The concept is an “ancient cultural tool” often found in literature, which is used to express humanity’s relationship to the land and natural surroundings (Gifford, “Post-Pastoral” 15; “Reading Strategies” 45). It is extended by approaches like the anti-pastoral and the post-pastoral. By primarily following Terry Gifford’s theoretical understandings, I will use these concepts for an analysis of the novel’s descriptions of nature, choice of language and narrative structure. I will mainly focus on the depiction of Hailsham, a boarding school for clones, because this offers insights into the characters’ ways of handling their fate and the importance of their childhood surroundings throughout their lives.